Experimental study on a novel photovoltaic thermal system using amorphous silicon cells deposited on stainless steel - Li, Jing; Ren, Xiao; Yuan, Weiqi; Li, Zhaomeng; Pei, Gang; Su, Yuehong; Su, Yuehong; Çağrı, Kutlu; Ji, Jie; Riffat, Saffa (Elsevier, 2018)
Amorphous silicon (a-Si) cells are able to perform better as temperature increases due to the effect of thermal annealing. a-Si cells have great potential to solve or ease the problems of high power temperature coefficient, large thermal stress caused by temperature fluctuation and gradient, and thick layer of conventional crystalline silicon cell-related photovoltaic/thermal (PV/T) collectors. In this paper, an innovative a-Si PV/T system is developed. It is the first time that a-Si cells deposited on stainless steel have been used in a practical PV/T system. The system comprises of two PV/T collectors. In each collector, there are 8 pieces of solar cells in series. Long-term outdoor performance has been monitored. Experimental results on the thermal efficiency Image 1, electrical efficiency Image 2 and I-V characteristic are presented. The peak instantaneous Image 3 was about 42.49% with the maximum Image 4 of 5.92% on April 2, 2017. The daily average Image 5 and Image 6 were 32.8% and 5.58%. Accordingly, Image 7 ,Image 8, Image 9 and Image 10 on October 27 were 43.47%, 5.69%, 38.65% and 5.22 %. During more than half a year operation, no technical failure of the system has been observed. The feasibility of the a-Si PV/T is preliminarily demonstrated by the prototype.